Pembangunan Sumber Daya Manusia Islam melalui Kebijakan Pemekaran Wilayah - Trihidayat , Rofiq (Journal Tafkirul Iqtishodiyyah, 2021)
Islam is a source of value in the organization. Islam views HRM as a core part of the organization related to employee behavior, such as relationships with one another, self-development, and more importantly, Islam builds organizational culture through employee behavior. Human resource development based on the Islamic concept is to form human beings with noble character, who always worship Allah who spreads mercy for the universe and is devoted to Allah. This is the direction of HR development goals according to the Islamic concept. Through regional expansion, good governance, quality of service to the community, proximity and timeliness of public services will improve